2009
DOI: 10.1007/s10840-008-9333-z
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular premature depolarizations triggered by incremental dose isoproterenol infusion: common electrocardiographic features

Abstract: Adrenergically mediated VPDs are frequent in patients without structural heart disease or VT and tend to originate from a few anatomic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In vivo, sympathetic imbalance and increased adrenergic drive are thought to underlie the PVCs that initiate post-MI arrhythmias, and adrenergic stimulation increases PVC incidence after MI (Rivas et al 2009). After MI, cardiac innervation undergoes extensive remodelling with denervation in the scar and partial denervation and nerve re-growth or sprouting in the peri-infarct region (Cao et al 2000;Rajendran et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, sympathetic imbalance and increased adrenergic drive are thought to underlie the PVCs that initiate post-MI arrhythmias, and adrenergic stimulation increases PVC incidence after MI (Rivas et al 2009). After MI, cardiac innervation undergoes extensive remodelling with denervation in the scar and partial denervation and nerve re-growth or sprouting in the peri-infarct region (Cao et al 2000;Rajendran et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nuria Rivas et al demonstrated that during isoproterenol infusion (a condition simulating the high adrenergic tone which occurs in acute MI patients) the most common site of origin of premature ventricular beats is RVOT [9]. Another possible mechanism to explain the RVOT origin of ventricular ectopic beats in this patient is the presence of myocardial ischemia due to severe right coronary ostial lesion, which usually gives off the conus arteriosus artery to supply blood to the RVOT.…”
Section: Discussionmentioning
confidence: 99%